ЎЗБЕК ХАЛҚ МАҚОЛЛАРИДА “МУҲАББАТ” КОНЦЕПТИ МАДАНИЯТ ФЕНОМЕНИ СИФАТИДА (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the role of the concept of "love" in Uzbek folk proverbs as a cultural phenomenon. Love is examined from a linguocultural perspective, within the framework of the relationship between language and culture, as a complex and multifaceted aspect of human life. Through proverbs that reflect the values of love, the moral, aesthetic, and social worldview of the Uzbek people is revealed. A comparative analysis of English and Uzbek proverbs highlights the differences in attitudes toward love and hatred across different cultures.